Long non-coding RNA OIP5-AS1 regulates smoke-related chronic obstructive pulmonary disease via targeting micro RNA -410-3p/IL-13. Issue 2 (20th December 2021) - Hao, Wenbo; Lin, Fei; Shi, Hanbing; Guan, Zhanjiang; Jiang, Yunfei
ABSTRACT: This investigation aimed to assess the levels of serum OIP5-AS1 and micro RNA-410-3p (miR-410-3p) in patients with chronic obstructive pulmonary disease (COPD) and their potential molecular mechanism. The levels of OIP5-AS1 and miR-410-3p as well as mRNA levels of IL-13 were measured. Pearson variable linear test was applied to analyze the correlations between forced expiratory volume in 1 second (FEV1) and OIP5-AS1. The receiver operating characteristic curve was used to predict the predictive possibility of OIP5-AS1. The viable cells were detected by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) and flow cytometry was used to detect the cell apoptosis. An enzyme-linked immunosorbent assay was performed to indicate the inflammatory situation of 16HBE cells. Luciferase activity assay was conducted to examine the relationships between OIP5-AS1 and miR-410-3p together with miR-410-3p and IL-13. Augmented levels of OIP5-AS1, declined levels of miR-410-3p, and enhanced expression of IL-13 were unveiled. The expression of OIP5-AS1 and miR-410-3p was related to the ratio of FEV1 respectively. OIP5-AS1 might serve as a diagnostic biomarker. Interference of OIP5-AS1 restored the abnormal cell viability, apoptosis, and inflammation in cigarette smoke extract (CSE)-stimulated 16HBE cells by regulating miR-410-3p and IL-13. OIP5-AS1 appeared to be a biomarker for distinguishing COPD patients from smokers. OIP5-AS1/miR-410-3p/IL-13 exerted function on the cell viability, apoptosis, and inflammation in CSE-steered cell models.